Analysis of Training and Work Performance on Career Development and Its Implications on Organizational Commitment and Job Satisfaction of Police Members of The HR Berau of Gorontalo Police: A Quantitative Analysis - Pranoyo, Tomy (IJBLE Scientific Publications Community Inc., 2024)
This quantitative study investigates the relationship between training, job performance, career development, organizational commitment, and job satisfaction among police officers in the HR Bureau of Gorontalo Regional Police. Data were collected through a survey from a sample of 157 officers and analyzed using SPSS version 26. Descriptive, correlation, regression, and mediation analyses were conducted to explore these relationships. The results showed significant positive correlations between training, performance, career development, organizational commitment, and job satisfaction. Regression analysis showed that both training and job performance significantly predicted career development, organizational commitment, and job satisfaction. Mediation analysis further demonstrated the mediating role of career development in explaining the relationship between training, job performance, organizational commitment, and job satisfaction. These findings underscore the importance of investing in training programs and developing career development pathways in police organizations to improve organizational outcomes and officer well-being.